New insights into the epigenetics of osteoporosis - Letarouilly, Jean-Guillaume; Broux, Odile; Clabaut, Aline (Genomics (San Diego, Calif.), 2019)
Osteoporosis is characterized by reduced bone formation and accumulation of adipocytes in the bone marrow compartment. The decrease in bone mass results from an imbalance between osteoclast-mediated bone resorption and osteoblast-mediated bone formation. The deficiency of bone cells to replace the resorpted bone can be due to a preferential differentiation of bone marrow stromal cells into adipocytes at the expense of osteoblasts. Consequently, the processes that control the differentiation of osteoclasts, osteoblasts and adipocytes play a crucial role in bone metabolism. It is known that epigenetic mechanisms are critical regulator of the differentiation programs for cell fate and moreover are subject to changes during aging. Here, we summarize recent findings on the role of epigenetics in the modulation of mechanisms that may be associated with osteoporosis. In particular, we focus on disturbances in the bone remodeling process described in human studies that address the epigenetic regulation of the osteoblast/adipocyte balance. •Epigenetic mechanisms regulate commitment, differentiation and activity of the cells of the bone marrow environment•DNA methylation and some miRNAs regulate bone remodeling in human osteoporosis•Histone modifications and miRNAs could explain the increase of bone marrow adiposity observed in human osteoporosis•Circulating miRNAs could be useful to investigate alterations of bone metabolism